Penerapan Limit Fungsi Mencari Keuntungan Maksimum dari Biaya Marginal - Nabilla, Zahra Syakira; Nursanti, Yuli Bangun Nursanti Bangun (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
Marginal costs are changes in total costs that occur as a result of changes in the quality of goods or services, either increasing or decreasing total costs. In production cost analysis, various types of costs used in processing goods or services will be evaluated to assess the extent to which capital will be used and the extent to which profits will be obtained. This analysis aims to plan its business, and companies can determine whether they will achieve maximum or minimum profits. This research was carried out through literature studies, where data sources and information were collected through collecting data from various references, reading, recording and processing data which became the basis for the research. Based on research, maximum profit will be achieved when MR = MC. Research shows that UD. Taufik Jaya Makmur Samarinda has not achieved maximum profits.